Preparation And Properties Of Mica Filled Virgin And Recycled Ethylene Propylene Diene Monomer (Epdm) Composites - Ishak, Sarah (2014)
The properties of single filler system (mica or talc) and hybrid filler system micaJCB and micaJHNTs filled virgin EPDM and recycled EPDM were investigated. In the first series, EPDM/mica composites show better tensile strength, tensile modulus, swelling resistance and thermal properties as compared to EPDM/taic composites and the optimum value of tensile strength and tensile modulus of EPDM/mica composite was found at 50 phr of fillers. In the second series, the result reveals tensile strength, tensile modulus, swelling resistance and thermal stability properties were better for EPDM/mica composites with silane compared to EPDM/mica composites without silane. The results for third series reported scorch time (t52) decreased with increasing r-EPDM content whereas minimum torque (ML)' maximum torque (MH), cure time (t90), swelling resistance and thermal stability showed the opposite trend. The optimum properties of tensile strength and tensile modulus occurred at EPDM70/r-EPDM30 blends ratio which was proven in SEM micrograph. In the last series, the results indicated t52 and t90 decreased, whereas, ML increased with the addition of CB and HNTs loading in the blends system.